COMMON NATIONAL CURRICULAR BASE AND SEXUAL AND GENDER DIVERSITY: DESCRIPTIONS - Franciscati da Silva, Caio Samuel [UNESP]; Leivar Brancaleoni, Ana Paula [UNESP]; Oliveira, Rosemary Rodrigues de [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
Considering the contemporaneousness of the National Curricular Common Base, the present investigation characterized possible conceptions about sexual and gender diversity present in the official document. Based on studies on sexuality in school and according to the qualitative paradigm, we performed a documentary analysis in which data were examined according to the Discursive Textual Analysis. The results indicate that the official document presents sexuality through biological understandings in spaces restricted to the Natural Sciences, along with concepts such as sexually transmitted infections and pregnancy. Gender diversity is silenced by the analyzed document, a fact aggravated by superficiality in the treatment of human rights.
Keywords: Sexuality; Gender; National Curricular Common Base